Assessment of the maturity concept in concrete with addition of rice husk ash - Akasaki, J. [UNESP]; Moraes, M. [UNESP]; Silva, C. [UNESP]; Fioriti, C. [UNESP]; Tashima, M. [UNESP] (Pontificia Universidad Catolica de Chile, 2016)
Steam curing is a process used to accelerate cement hydration reactions with the purpose of enhancing the mechanical strength of concrete at early ages, since hydration reactions are temperature dependent. To evaluate the influence of temperature on the development of mechanical properties of concrete the maturity concept was used. This method estimates the development of these properties according to the temperature history of concrete along the curing process. The temperature influence is indicated through the apparent activation energy (AE) value. The higher the AE value, the higher the energy amount will be necessary to start reactions, and thus the velocity of these reactions will be affected by temperature. This work is based on an experimental study of steam-cured concrete made with 5% and 10% of rice husk ash (RHA) addition in which the development of some mechanical properties was investigated. The rice husk ash used was obtained from uncontrolled combustion of rice husk, in an open chamber, without any temperature control or burning time. The mechanical property investigated was the compressive strength. Results indicate the influence of RHA addition and its dosage on the hydration reactions of cement and the mechanical properties of steam-cured concretes.
Evaluación del concepto de madurez en el hormigón con adición de cenizas de cascarilla de arroz
Keywords: Concrete; Maturity; Rice husk ash; Steam curing